Is tooth loss important when evaluating perceived general health? Findings from a nationally representative study of Costa Rican adults - Barboza Solís, Cristina (2019)
Objectives. Although previous studies have shown that oral diseases can impact certain systemic conditions, dental care has been historically separated from medical healthcare organizations in middle‐income countries. There is a lack of research approaches which test the independent relationship between oral health and multidimensional measures of general health. This study analyses the influence of tooth loss on self‐rated health (SRH), hypothesizing that, relatively to certain morbidity conditions, tooth loss is a health condition associated with SRH. This study analyses the influence of tooth loss on self‐rated health (SRH), hypothesizing that, relative to certain morbidity conditions, tooth loss is a health condition associated with SRH. Methods. Data were obtained from the Costa Rican Longevity and Healthy Aging Study 1945‐1955 Retirement Cohort, a national representative longitudinal survey including residents born between 1945 and 1955. The association between severe tooth loss and SRH was analysed cross‐sectionally using the first wave of the study conducted in 2010. A multivariable logistic regression, adjusted for potential confounders, was performed on 2797 participants. A counterfactual analysis was additionally performed to illustrate the theoretical change on SRH prevalence—if all the participants were not to have had severe tooth loss. Results. Severe tooth loss was associated with poor SRH, after adjustment for smoking, morbidity, biomarkers and performance‐based physical measures. The counterfactual analysis showed that severe tooth loss was the fifth most important morbidity condition in determining poor SRH. Declaring a poor SRH would have been decreased by 2.0 percentage points if those participants having severe tooth loss had shared the same risk pattern of those who had not lost the majority of their teeth. Conclusion. Individuals consider their oral health status to a similar extent as other morbidity conditions when evaluating their general health. A stronger focus on oral health, and its impact on general health, could lead to better planning of national resources, thereby improving accessibility to health care and modifying prevailing conceptions of health care in low‐ and middle‐income countries.